Paper trails: The development of management accounting at Alex. Cowan & Sons Ltd, Penicuik, 1779–1965. (February 2013) - Ding, Ying Yong; McKinstry, Sam
This article examines the development and operation of management accounting in a significant UK papermaking firm, Alex. Cowan & Sons Ltd, of Penicuik, Scotland, over a period in excess of 150 years, and is the first known study of management accounting within the UK paper industry in the academic historical literature. It explains developments in the firm's management accounting systems in the context of internal and external factors affecting the firm and in terms of the key individuals who made changes, by means of the Systems/Contingency model. Based on the Cowan case, the authors hypothesize that management accounting across the UK papermaking industry is likely to have been well developed for a long period of time, in view of the commercial pressures under which the industry operated.